Penerapan REST API dalam Pengembangan Aplikasi Pemesanan Rental Mobil berbasis Web dan Mobile (Studi Kasus: CV. Dwi Cipta Rent Car) - I Gede Merta Ariantara; Issa Arwani; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Vehicle rental businesses have sprung up and making the competition fiercer, business owners are required to innovate, for example by using technology in completing their operational activities. CV. Dwi Cipta Rent Car is a business that operates in the field of vehicle rental services, specifically cars. On the CV. Dwi Cipta Rent Car customer who want to make a rental sometimes must first come to the rental shop to make an order, then come back to pick up the booked car according to the specified time when making the order, and sometimes the vehicle that the customer wants to order is already up. In addition, customer transactions are still done manually by recording customer ordering vehicle data in the rental journal. Based on the existing problems, in this study an application was made regarding rental car reservation. This application was developed utilizing API (Application Programming Interface) technology, namely REST API. The application developed by the waterfall software development method, on the web and mobile platforms. The testing is done with validation testing and compatibility testing. Validation testing results using the black-box testing method got valid results for all the functional needs that have been tested. While for the compatibility testing, the result is the system can run on various browsers for the web, and various different API levels for mobile application.